Business as Usual? Bail Decision Making and "Micro Politics" in an Australian Magistrates Court. Issue 2 (9th December 2016) - Travers, Max
Abstract : Between the 1970s and 1990s, political scientists in the United States pursued a distinctive research program that employed ethnographic methods to study micro politics in criminal courts. This article considers the relevance of this concept for court researchers today through a case study about bail decision making in a lower criminal court in Australia. It describes business as usual in how decisions are made and the provision of pretrial services. It also looks at how traditionalists and reformers understood business as usual, and uses this as a critical concept to make visible micro politics in this court. The case study raises issues about organizational change in criminal courts since the 1990s, since there are fewer studies about plea bargaining and more about specialist or problem‐solving courts. It is suggested that we need a new international agenda that can address change and continuity in criminal courts.